The Trend of Mathematics Teaching Method Has Change From Fragments To Systematics - Lin Yi; Zhou Ying; Tommy Tanu Wijaya (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
According to the school observation in China, There are still fragmentation and superficiality problems in front-line teachers’ mathematics teaching method. The reason is that the general system theory has not been rooted in the mathematics teaching method. This study aims to develop Dick-Carey model of systematic design and used in the learning activity. Based on system analysis model, Dick-Carey model of systematic design, and the “Six Questions” cognitive concepts, this paper tries to construct a systematic plan of teaching mathematics. In order to restore the structure, improve the breadth, depth and openness of teaching plan and to promote the systematic model into better teaching method. At the same time, taking the design of "intersecting lines" as an example, this paper explores the effective strategies of systematic design in mathematics teaching.